2023
DOI: 10.1097/hep.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

SULT2B1-CS-DOCK2 axis regulates effector T-cell exhaustion in HCC microenvironment

Abstract: Background and Aims: HCC is a malignant disease. Compared with tyrosine kinase inhibitors (the classical therapy), immune checkpoint inhibitors are more effective in the treatment of HCC, despite their limited efficacy. Among these restricted factors, exhaustion of tumor-infiltrated lymphocytes, especially CD8+ T cells, is a core event. We aimed to determine the key factors contributing to CD8+ T-cell infiltration in HCC and investigate the underlying mechanisms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…NCKAP1L impedes HCC proliferation by intensifying the Rb1/p53 pathway 36 . DOCK2 has been identified as a potential marker for CD8 + T cell infiltration in HCC 37 . In addition, antigen presentation by MHC class II (HLA‐DMB, HLA‐DRA, HLA‐DRB5) is activated in LR‐HCC.…”
Section: Resultsmentioning
confidence: 99%
“…NCKAP1L impedes HCC proliferation by intensifying the Rb1/p53 pathway 36 . DOCK2 has been identified as a potential marker for CD8 + T cell infiltration in HCC 37 . In addition, antigen presentation by MHC class II (HLA‐DMB, HLA‐DRA, HLA‐DRB5) is activated in LR‐HCC.…”
Section: Resultsmentioning
confidence: 99%
“…19 A recent study found that HCC cells with expressed SULT2B1 inhibited DOCK2 enzyme activity, allowing tumor cells to acquire immunotherapy tolerance. 41 For advanced HCC, treatments have ranged from molecularly targeted monotherapies to tumor immune monotherapies to combination therapies. 42 In our study, the CAF high cluster had a better response to sorafenib and sunitinib that inhibit angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues revealed that the exhaustion of infiltrated CD8 + T cell in tumors is related to suppressed DOCK2 enzymatic activity in T cells in hepatocellular carcinoma (HCC), which is mediated by cholesterol sulfate synthesized by sulfotransferase 2B1 (SULT2B1) in tumor cells. They identified that CD8 + T‐cell exhaustion mediated by DOCK2 inactivation can be reversed by tolazamide 125 . As an RNA‐binding protein that regulates neuronal RNA stability and translation, fragile X mental retardation protein (FMRP), is highly expressed in human cancers and may function in antitumor immunity.…”
Section: Potential Targets Modulating Tumor Immune Responsementioning
confidence: 99%